2013
DOI: 10.1007/s13197-013-1194-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc enrichment of whole potato tuber by vacuum impregnation

Abstract: Zinc is a nutritionally essential truce element, and thus zinc deficiency (ZD) severely affects human health. More than 25% of the world's population is at risk of ZD. This study was initiated to examine the use of the vacuum impregnation (VI) technique for enriching zinc content of whole potatoes; the effect of vacuum time, restoration time, steam-cooking and storage at 4°C on the zinc content of VI whole potatoes was evaluated. Whole potato tubers were immersed in a 9 g/ 100 g zinc (zinc gluconate) solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 37 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…It can be concluded that during cooking, a higher iron leakage was observed for US-VIprocessed samples compared to VI. During vacuum stage, because of a negative pressure, the internal gas content within the sample pores is expanded and partially flows out due to the capillary penetration (Erihemu et al, 2015). In resting time step, due to an increase in pressure, the residual gas is compressed and the external liquid sucks into the pores (Zhao & Xie, 2004).…”
Section: Iron Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that during cooking, a higher iron leakage was observed for US-VIprocessed samples compared to VI. During vacuum stage, because of a negative pressure, the internal gas content within the sample pores is expanded and partially flows out due to the capillary penetration (Erihemu et al, 2015). In resting time step, due to an increase in pressure, the residual gas is compressed and the external liquid sucks into the pores (Zhao & Xie, 2004).…”
Section: Iron Contentmentioning
confidence: 99%
“…Various applications of VI in food have been investigated recently in numerous studies. These studies have mainly attended product development through candying (Barat, Talens, Barrera, Chiralt, & Fito, 2002), osmotic treatments (Fito & Chiralt, 2000;Fito, Chiralt, Barat, et al, 2001;Fito, Chiralt, Betoret, et al, 2001;Moreno et al, 2004), food salting process (Barat, Grau, Ib añez, & Fito, 2005;Chiralt et al, 2001;Gonz alez-Martínez, Chafer, Fito, & Chiralt, 2002), and food fortification with vitamin E and minerals (Park, Zhao, Leonard, & Traber, 2005), with ascorbic acid (Hironaka et al, 2011), with iron (Erihemu, Hironaka, Oda, & Koaze, 2014), with calcium (Gras, Vidal, Betoret, Chiralt, & Fito, 2003), and with zinc (Erihemu, Hironaka, Koaze, Oda, & Shimada, 2015).…”
mentioning
confidence: 99%
“…Other functional foods have also been produced. For example, β-carotene enriched apples (Santacruz-Vazquez et al, 2008), zinc enriched whole potato tuber (Erihemu et al, 2015), selenium-enriched cabbage (Haizhen et al, 2006), calcium and iron-fortified apples (Barrera et al, 2004). The ability to control the osmotic process conditions (the type of solution/osmo-active agents) step provides the versatility in the use of osmo-convective dehydration technology for new product development.…”
Section: Effects Of Osmo-convective Drying On Nutrients Of Dried Fruitsmentioning
confidence: 99%
“…casie viable cells in dried and stored products was greater than 10 6 cfu/g (Betoret et al, 2003). Other functional foods have also been produced, for example, β-carotene enriched apples , zinc enriched whole potato tuber (Erihemu et al, 2015), selenium enriched cabbage (Haizhen et al, 2006), calcium and iron fortified apples (Barrera et al, 2004) etc. Recently, the use of liquid smoke in imparting smoky flavor in brining and osmotic dehydration of meat and fish is another area receiving attention (Alcicek & Atar, 2010).…”
Section: Latest Research Interest In Osmo-convective Dehydrationmentioning
confidence: 99%
“…One important advantage of OD step in effective osmo-convective dehydration "hurdle technology", is the ability to control the osmotic solution (OS) to impart the desired organoleptic, nutritive and nutraceutical properties, including anti-microbial quality in the resultant food formulation. Many researchers have taken the advantage of OD to infuse different nutrients and edible compounds into food (dried or intermediate) (Barrera, et al, 2004;Betoret, et al, 2003;Erihemu, et al, 2015;Haizhen, et al, 2006;. In this vein, we explored the use of food grade refined liquid smoke (RLS), as an anti-microbial agent and flavor additive in osmo-convective dehydration to produce "dried smoky apple snacks".…”
Section: Introductionmentioning
confidence: 99%